PD‐L1 overexpression in ampulla of Vater carcinoma and its pre‐invasive lesions. Issue 3 (29th June 2017) - Saraggi, Deborah; Galuppini, Francesca; Remo, Andrea; Urso, Emanuele D L; Bacchin, Deborah; Salmaso, Roberta; Lanza, Cristiano; Bao, Riccardo Q; Fanelli, Giuseppe N; Guzzardo, Vincenza; Luchini, Claudio; Scarpa, Marco; et al.
Abstract : Aims: PD‐1/PD‐L1 checkpoint immunotherapy has been proposed recently as a promising treatment in relapsed/refractory disease, used eventually in combination with traditional chemotherapy in different cancer settings. To date, no data are available concerning PD‐L1 expression in ampulla of Vater carcinoma and its pre‐invasive lesions. Methods and results: We assessed the immunohistochemical expression of PD‐L1 in a series of 26 ampullary adenocarcinomas, 50 ampullary dysplastic lesions and 10 normal duodenal mucosa samples. Moreover, in all cases DNA mismatch repair proteins status was investigated. PD‐L1 was expressed in seven of 26 (26.9%) invasive carcinomas and three of 50 (6.0%) dysplastic samples. Most of the PD‐L1‐positive tumours (seven of 10) were intestinal‐type and poorly differentiated (G3). The number of PD‐L1‐positive stromal lymphoid cells was significantly higher in dysplastic and invasive lesions than in the normal samples ( P = 0.011). Nineteen dysplastic lesions and eight invasive carcinomas did not show any evident epithelial or stromal PD‐L1 expression. Four of the carcinomas were mismatch repair‐deficient and two of these were PD‐L1‐positive. Furthermore, mismatch repair‐deficient lesions showed a significantly higher average of PD‐L1‐positive stromal lymphoid cells than those of neoplastic PD‐L1‐negative samples (62.8 versus 21.6; P < 0.001). Conclusions: The present results suggest a role of the PD‐1/PD‐L1 axis in ampullary adenocarcinomas, and therefore this may also prompt consideration of checkpoint immunotherapy as a novel promising treatment for these tumours.